Organ donation attitudes of relatives of patients in the wards and intensive care units: Will you be a life? - Altuntas, Gulsum; Celik, Fatma; Aksu, Ahmet; Ozcelik, Gulsum; Dogan, Furkan; Demirel, Ismail (Turkish Society Intensive Care, 2025)
Objective: Inadequate organ donation rate is still an obstacle to organ transplantation. Lack of information and negative attitudes are the most important obstacles. Having a patient in intensive care unit may change the perspective and create sensitivity. We aimed to compare the perspectives on organ donation between relatives of patients in intensive care and inpatient services. Material and Method: It is a cross-sectional descriptive survey study. Group I: relatives of patients hospitalized in the 3rd level intensive care unit, and Group II: relatives of patients at inpatient services. Written informed consents were obtained. Questions were consisted of;1-Demographic data, 2- Level of knowledge about organ donation, 3-Attitudes and behaviors regarding organ donation. Results: There was a significant difference between the groups regarding the purpose of organ donation (p=0.006). The overall rate of support for organ donation by Group I (75.9%) was significantly higher than the Group II (18.7%) (p<0.001). Conclusion: The attitudes of relatives of patients in intensive care, towards organ donation are better than those who do not have patients in intensive care. Education and awareness-raising activities on organ donation should be carried out more intensively and effectively. Specially designed questionnaires, psychological support, empathy, respectful and early communication can also be effective.
Keywords: organ donation; intensive care; questionnaire; attitudes